THE BUSINESS POTENTIAL OF ANCHOVY PRODUCTION FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS IN SEDANAU, BUNGURAN BARAT DISTRICT, NATUNA REGENCY - Mamek Romadon; Kartubi; Nurdian Setiawan (SOSIOEDUKASI, 2026)
The anchovy (ikan bilis) production industry in Sedanau, Bunguran Barat District, Natuna Regency, represents a significant livelihood source for the local coastal community, yet its production practices have never been evaluated against the normative standards of Islamic economics. This study aims to examine the anchovy production process in its full operational detail and to assess that process from the perspective of Islamic economics, particularly regarding the principles of halal, tayyib, business honesty, food safety, and social responsibility. Employing a qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman & Saldaña. The study finds that the production process operates through four stages, harvesting, boiling, drying, and marketing, with considerable economic efficiency. However, three critical normative deviations are identified: the use of deteriorating raw material in violation of the tayyib and shiddiq principles, the repeated reuse of boiling water that compromises food safety, and the disruptive placement of drying mats in public spaces that inflicts harm on the surrounding community. These findings carry direct implications for SDG 2, SDG 3, SDG 8, and SDG 10, underscoring the urgent need for Islamic economic literacy and production guidance in informal coastal food enterprises.